A situation awareness interface for a bi-wheeled industrial hovercraft: design, development and evaluation - Corujeira, José Gouveia Pereira (2013)
The intention of this thesis is to develop a prototype interface that enables an operator to control a bi-wheeled industrial hovercraft that will work within a fusion power plant if the automation system fails. This fusion power plant is part of the ITER project a conjoint effort of various industrialized countries to develop cleaner sources of energy. The development of the interface prototype will be based on situation awareness concepts, which provide a means to understand how human operators perceive the world around, then process that information and make decisions based on the knowledge that they already have and the projected knowledge of the reactions that will occur in the world in response to the actions the operator makes. Two major situation awareness methods will be used, GDTA as a means to discover the requirements the interface needs to solve, and SAGAT to conduct the evaluation on the three interfaces. This technique can isolate the differences an operator has in situation awareness when presented with relevant information given by each of the three interfaces that were built for this thesis. Where the first interface presents the information within the operator’s focal point of view in a pictorial style, the second interface shows the same information within the same point of view has the first interface but only shows it in a textual manner. While the third interface shows the relevant information in the operator’s peripheral field of view. Also SAGAT can provide insight on the question to know if providing the operator with feed-forward information about the stoppage distances of the bi-wheeled industrial hovercraft has any effect on the operator’s decision making.